Development and validation of the participatory approach questionnaire (PARTAQUE) in cancer teams: a ready-to-use tool for enhancing the quality of work life for caregivers - Lejeune, Julien; Galy, Anaïs; Fouquereau, Evelyne; Jeoffrion, Christine; Aubouin-Bonnaventure, Julia; Coillot, Hélène; Bordarie, Jimmy; Seizeur, Romuald; Colombat, Philippe (Frontiers in Psychology, 2025)
The Participative Approach (PA) has demonstrated the potential to enhance both the quality of work life and the quality of care within French cancer teams. Whilst a number of studies have demonstrated that the participatory approach exerts a positive impact on all stakeholders within the care context, none of them have thus far used a measurement of the PA that has been scientifically validated. Therefore, the aim of this research was to develop and validate the PARTAQUE (Participatory Approach Questionnaire) and to assess its psychometric properties. This objective was pursued by conducting three independent studies in French healthcare organizations. The assessment of the factorial structure of the scale confirmed a good fit with a second-order factor model, and the test of convergent and predictive validity showed consistent relationships with theorized outcomes (e.g., attitudinal and behavioral work outcomes, occupational health indicators). The implications for research and practice are then discussed.